Buddhism and Christianity, their Inner Affinity - Achandy, Paul (Journal of Dharma, 1984)
Antony Fernando Buddhism and Christianity, their Inner Affinity Colombo: Ecumenical Institute for Study and Dialogue, second ed. 1983, p. 133.